Integrated Design and Optimization of Water-Energy Nexus: Combining Wastewater Treatment and Energy System - Rezazadeh Kalehbasti, Pouya; Lepech, Michael D.; Criddle, Craig S. (Frontiers in Sustainable Cities, 2022)
Designing more sustainable urban infrastructure is an essential topic in practice and research. While many have tried to address this challenge by focusing on sustainability of either supply or demand in a single infrastructure system, few studies have integrated the decisions for both supply and demand across several infrastructure. This paper proposes a novel method to design and optimize the hourly demand and supply of integrated energy and water system in an urban district for environmental and economic sustainability. This modular framework concurrently designs the optimal building mix of an urban district and the systems supplying the district with wastewater treatment, cooling, heating, and electricity. The model is tested on a sample neighborhood from San Francisco, California, with 21 building prototypes, 32 combined heating and power engines, 16 chillers, and 3 wastewater treatment systems (a central treatment plant and two decentralized membrane-based systems). The results of this study show that the median values of normalized life-cycle cost, social cost of carbon, annual energy demand, and annual wastewater production of the integrated designs of water-energy system are, respectively, 20%, 75%, 8%, and 20% lower than those of the traditional segregated designs. The results also demonstrate the economic and environmental viability of using decentralized advanced treatment in urban areas when energy system, wastewater treatment, and building mix are designed together.